Follow-up After Proximal Femur Fracture Fixation—We Need to Do Better - Emilio Feijoo, MD; Adele Bloodworth, BS; Gerald McGwin, PhD; David Patch, MD; Shawn R. Gilbert, MD; Kevin A. Williams, MD; Shane Strom, MD; Michael J. Conklin, MD (Journal of the Pediatric Orthopaedic Society of North America, 2025)
Background: Long-term follow-up after proximal femur (femoral neck) fracture is required to screen for complications, especially avascular necrosis (AVN). The purpose of this study was to evaluate sociodemographic characteristics as risk factors for lost-to-follow-up (LTFU) status following proximal femur fractures. Methods: This retrospective case series included patients under the age of 18 years treated at a children’s hospital for proximal femur fractures. Data were collected from the electronic medical record (EMR). Area deprivation index (ADI) was determined using patient addresses. Patients were designated as LTFU if they followed up for less than 2 years from the initial operation without being discharged by their surgeon as determined by the last clinic note. The most recent imaging was evaluated for AVN. Results: Forty-two patients (26 male) were included. Twenty-four were in the appropriate follow-up (AFU) group while 18 were in the LTFU (42.9%) group. Average follow-up for the AFU and LTFU groups was 822 (235-3054) days and 103 (2-263) days, respectively. There were seven cases of AVN, all in the AFU group. AVN was seen at an average of 230 days from injury. The LTFU group had a significantly higher proportion of Medicaid and uninsured patients. Commercial/private insurance status was associated with a significantly longer follow-up period (940.6 days) compared with Medicaid patients (295.9 days) and uninsured patients (347.7 days). Both state and national ADI were significantly greater in the LTFU group. Upon multivariate analysis adjusting for distance from clinic, both mean state and national ADI remained significantly greater in the LTFU group. Conclusions: This study highlights disparities in follow-up of pediatric proximal femur fractures. Insurance status and ADI were significantly associated with follow-up. Quality improvement initiatives should be implemented to improve follow-up. Further studies should assess which social determinants most impact the follow-up status. Key Concepts: (1) Close follow-up after femoral neck fracture fixation is strongly recommended for avascular necrosis surveillance. (2) A variety of interventions can be considered in patients who develop avascular necrosis if the pathology is detected early through regular follow-up. (3) Certain populations may be more vulnerable to lost to follow-up status. (4) Quality improvement initiatives should be implemented to improve compliance with recommended follow-up after femoral neck fracture fixation. (5) Additional studies should be conducted to ascertain which social determinants of health modify a patient’s ability to attend follow-up appointments. Level of Evidence: IV